i10 sporen van de avant-garde. - Alma, Peter; Arp, Hans (Jean); Baldwin, Roger N.; Benjamin, Walter; Berkman, Alexander; Bloch, Ernst; Bois, Yve-Alain; Bolliger, Hans; Bool, Flip; Braak, Menno ter; Bulhof, Francis; Casciato, Maristella; et al. (Heerlen : Algemeen Burgerlijk Pensioenfonds, 1994)
Alma, Peter ; Arp, Hans (Jean) ; Baldwin, Roger N. ; Benjamin, Walter ; Berkman, Alexander ; Bloch, Ernst ; Braak, Menno ter ; d'Ebneth, Lajos ; Domela, César ; van Eesteren, Cornelis ; Ehrenburg, Ilja ; Gabo, Naum ; Gumbel, Emil J. ; Henri, Florence ; Holst, Henriëtte Roland ; Huszar, Vilmos ; Ivens, Joris ; Kandinsky, Wassily ; Krenek, Ernst ; van der Leck, Bart ; Lehning, Arthur ; de Ligt, Bart ; Lissitzky, El ; Malevich, Kasimir ; Marsman, Hendrik ; Moholy, Lucia ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Nettlau, Max ; Oud, Jacobus ; Palucca, Gret ; Pijper, Willem ; Rietveld, Gerrit ; Romein, Jan ; Schapiro, Alexander ; Schuitema, Paul ; Schwitters, Kurt ; Segal, Arthur ; Slauerhoff, Jan Jacob ; Stam, Mart ; Vantongerloo, Georges
biografie
Duits
Engels
Frans & Nederlands & Duits
Nederlands
boek